Gerontology And Its Implications For Adult Education - Olajide, O. E; Ayantunji, Mojirade M. (European Scientific Journal, ESJ, 2016)
The study of the elderly is a recent field of study and as such, has not been given its proper place in the human society. The elders or the retired workforce are in most cases regarded as people who have exhausted all their potentials of life during their services at their various places of work. They can no longer make meaningful contributions to the development of the society. This paper however, takes the position that adult education has a role to play in making people understand and appreciate the fact that the elderly or retired elderly people can still contribute meaningfully to the betterment of the human society. They should as well appreciate the message coded in gerontology. This paper explains the concept of ageing and its perspectives, gerontology and its implications to adult education. This paper concluded that adult education could be used in reducing the challenges faced by the elderly people by providing them with appropriate programmes of guidance and also proper counselling that will help in adjusting and assisting them to cope with the declining functions of the organ of the body and contribute meaningfully to improve the society.